User resistance factors in post ERP implementation - Salih, Sayeed Haider (2013)
Enterprise resource planning (ERP) systems are becoming mature technologies to support inter- and intracompany business processes. However, one of the factors frequently cited as the major reason for the failure of ERP system in post implementation is “User Resistance”. ERP implementation doesn’t finish after Go-Live, instead the real test of system starts when user begins using the system. The main purpose of this study is to investigate user resistance factors in ERP post implementation stage and the influence between the factors associated with the research model. Correlation analysis is used to investigate the influence between user resistances. To achieve this objectives quantitative method were conducted with 95 ERP end users. The result shows Resistance due to change, Change in Job content, User Expectations, Increased efforts, Lack of Education and User training, Usability issues and resistance to technology, Lack of user involvement in the development process, and Lack of communication between top management and end users are the factors behind user resistance. Recommendations and guideline to avoid user resistance in ERP post implementation are also presented. The benefits and outcomes of this study shall aid organizations to overcome user resistance in post ERP implementation.